Seeking Justice: How VAWA Reduced the Stronghold Over American Indian and Alaska Native Women - Hartman, Jennifer L. (Violence against women, 2021)
The Violence Against Women Act (VAWA), originally passed in 1994, was successfully reauthorized in 2000, 2005, and 2013. Over time, VAWA altered the environment for many victims who had previously suffered in silence. This article focuses on how VAWA impacted American Indian (AI) and Alaska Native (AN) victims of dating and domestic violence. AI and AN women experience these crimes at a rate higher than the national average, yet they are often denied justice due to the interplay of federal and state laws and tribal sovereignty. VAWA affirmed tribes’ sovereign authority to exercise criminal jurisdiction over non-Indians who commit crimes against AI and AN victims on tribal lands. This article also discusses future steps to enhance justice reforms.